Studies on diverse genotypes of amaranth (Amaranthus species) for their antioxidant and nutritional activities - YADAV, R K; JOSHI, SUBODH; KUMAR, RAJ; VARSHNEY, RICHA; JAIN, VARSHA (The Indian Journal of Agricultural Sciences, 2013)
An investigation was carried out with eight diverse genotypes of amaranth (Amaranthus species) to estimate thebiochemical composition (including anthocyanin, total carotenoids, ascorbic acid, antioxidant, i e Ferric ReducingAntioxidant Power (FRAP) and Cupric ion Reducing Antioxidant Capacity (CUPRAC) and total phenolic content) atIARI, New Delhi, during 2011. Among genotypes, anthocyanin ranged from 5.33 mg/100 g of fresh sample (Renu Sree)to 40.81 mg/100 g (Pusa Lal Chaulai). Maximum ascorbic acid was recorded in Co 1 (81.2 mg/100 g), followed by PusaKirti (78.4 mg/100 g).Total carotenoids were maximum in Pusa Lal Chaulai (69.41 mg per 100 g). Total antioxidantactivity measured by CUPRAC and FRAP showed that three genotypes, Pusa Lal Chaulai, Krishna Sree and Co 1, hadhigher value of antioxidant in CUPRAC method, however in FRAP method highest antioxidant activity was recorded inPusa Lal Chaulai (13.157 Âµmol ascorbic acid equivalent, AAE/g), followed by Pusa Kirti (13.033 Âµmol AAE/g). Totalphenolic content was recorded maximum in Co 1 (1 411.62 Î¼g gallic acid equivalent (GAE) per g), followed by Pusa LalChaulai (1 138.5 Î¼g GAE per g). By considering all, it was observed that Co 1, Pusa Lal Chaulai, Pusa Kirti and Renu Sreewere potential genotypes and hence may be utilized for improvement of amaranth for high nutritional activity.